before yesterday about today - -, - (project baikal, 2011)
Einem Prognosis. Moscow of the Future: a Look from 1914A City of the Present and the FutureUrbanismMoscow of 1945Moscow on the Construction SiteRuins of the Future in the City of GhostsKonstantin Lidin Foresight of Broken Dreams